Effects of genipin crosslinking on mechanical cell-matrix interaction in 3D engineered tendon constructs. (July 2021) - Giannopoulos, A.; Svensson, R.B.; Yeung, C.Y.C.; Kjaer, M.; Magnusson, S.P.
Abstract: It is well known that cells can generate endogenous forces onto the extracellular matrix, but to what extent the mechanical properties of the matrix influences these endogenous cellular forces remains unclear. We therefore sought to quantify the influence of matrix rigidity on cell-matrix interactions by inducing cross-links using increasing concentrations of genipin (0.01–1 mM) or by blocking cross-link formation using beta-aminopropionitrile (BAPN) in engineered human tendon tissue constructs. The cell-matrix mechanics of the tendon constructs were evaluated as cell-generated tissue re-tensioning and stress-relaxation responses using a novel custom-made force monitor, which can apply and detect tensional forces in real-time in addition to mechanical failure testing. Genipin treatment had no influence on the biochemical profile (hydroxyproline, glycosaminoglycan and DNA content) of the constructs and cell viability was comparable between genipin-treated and control constructs, except at the highest genipin concentration. Endogenous re-tension after unloading was significantly decreased with increasing genipin concentrations compared to controls. Mechanical failure testing of tendon constructs showed increased (56%) peak stress at the highest genipin concentration but decreased (72%) with BAPN treatment when compared to controls. Tendon construct stiffness increased with high genipin concentrations (0.1 and 1 mM) and decreased by 70% in BAPN-treated constructs, relative to the controls. These data demonstrate that human tendon fibroblasts regulate their force exertion inversely proportional to increased cross-link capacity but did so independently of matrix stiffness. Overall, these findings support the notion of an interaction between cell force generation and cross-linking, and thus a role for this interplay in mechanical homeostasis of the tissue.